PENYELESAIAN SENGKETA TANAH TERLANTAR MELALUI PENGADILAN OLEH PEMEGANG HAK GUNA USAHA (HGU) - Sulis Anita (Magister Kenotariatan Program Pascasarjana Universitas Islam Malang, 2022)
The case of abandonment of land carried out by PT. Sarana Subur Agrindotama as the Holder of Cultivation Rights (HGU) in South Kalimantan because it does not utilize state land designated for oil palm plantations. It is stated based on the Decree of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency No.1/PTT-HGU/KEM-ATR/BPN/2017 dated June 6 2017, concerning the Stipulation of Abandoned Land originating from Cultivation Rights Number 01/Tanah Laut over name of PT. Means Subur Agrindotama is located in Kandangan Lama Village, Kuringkit, Batu Furnace and Bumi Asih, Panyipatan District, Tanah Laut Regency, South Kalimantan Province. The method used in this study is the case approach method, by using this method the researcher is able to answer the problems that occur and the researchers also try to build legal arguments regarding the cases that occurred in South Kalimantan. Regarding the abandonment of this land, PT. Sarana Subur Agrindotama which stated that they did not abandon the land, but because the land was still difficult to reach and heavy equipment was still limited. In addition, the people who bordered and were in the village where the land was located had already opened fields for gardens. The settlement of cases carried out is PT. Sarana Subur Agrindotama filed a lawsuit to the Jakarta State Administrative Court to cancel the Ministerial Decree. However, based on the report on the results of the identification and research of abandoned land indicated by the Tanah Laut Land Office, it was stated that the land in South Kalimantan was identified as abandoned land. So that Decision Number 182/G/2017/PTUN.JKT rejected PT. Sarana Subur Agrindotama, which stated that PT. Sarana Subur Agrindotama has abandoned land in South Kalimantan.